Genetic variability, heritability and genetic advance of some yield contributing characters in lablab bean (Lablab purpureus L. Sweet) (Journal of Bio-Science, 2019)
Eleven genotypes of lablab bean were put into trial in four consecutive years to evaluate genetic variability among characters. Genotypic and phenotypic coefficient of variability, heritability and genetic advance as percent of mean were estimated for four yield contributing characters i.e. number of flowers per plant, number of pods per plant, average number of seed per pod and average pod weight (gm). The range of variation was highly pronounced in all the four characters. Without grouping the presence of wide range of variation in these characters indicate that they are quantitative in nature and are under polygenic in control. Mean with standard error showed differences between the varieties and co-efficient of variability in percentage (CV%) indicates certain degree of variability for the characters studied which are prerequisite in breeding research. Genotypes were found to be significantly different for all characters in analysis of variance. Low differences between PVC and GVC shows that these traits are less influenced by environment and the effect of heritable components were high. High heritability coupled with high genetic advance as percent of mean was recorded by number of flowers per plant, number of pods per plant and average pod weight (g) indicates additive action of genes controlling them.J. bio-sci. 28: 13-20, 2020